Mediating effects of heart rate variability on the association between chronic stress, cardiorespiratory fitness and working memory maintenance - Vera Nina Looser; Sebastian Ludyga; Markus Gerber (Bern Open Publishing, 2023)
Young adulthood is a demanding developmental stage during which an individual is required to learn to adequately respond to physical and psychosocial stressors (Malter Cohen et al., 2013). High degrees of chronic stress have been shown to have detrimental effects on physical and mental health outcomes in young adults, accompanied by decreases in academic achievement and subjective well-being (Bayram & Bilgel, 2008; Malter Cohen et al., 2013). While effects of acute stress on neurocognitive functioning have been examined, documentation on effects of prolonged stress exposure on working memory is scarce. While chronic stress may impair working memory, empirical evidence supports the assumption that exercise targeting cardiorespiratory fitness has the potential to buffer harmful effects of stress on working memory performance (Loprinzi & Frith, 2019). According to the Neurovisceral Integration Theory, shared neurophysiological areas are involved in cardiac autonomic control as well as the modulation of attentional and emotional regulatory processing (Forte et al., 2019). Therefore, heart rate-variability (HRV) may be a physiological correlate mediating the association between chronic stress, cardiorespiratory fitness and working memory maintenance. The present study investigated the mediating role of resting heart rate-variability on the association between chronic stress, cardiorespiratory fitness and working memory maintenance in young healthy adults. Working memory maintenance was assessed in N = 115 healthy adults (48% female) aged 18 to 35 years (M = 24.1, SD = 3.8) using a modified version of the Sternberg task with low (3 items) and high cognitive load (6 items). Additionally, the Åstrand test was conducted on a bicycle ergometer to estimate maximal oxygen consumption (VO2max). Resting HRV was recorded using electrocardiography. The LF/HF ratio was extracted for mediation analyses. Path analysis revealed a significant association between cardiorespiratory fitness and accuracy on high cognitive load trials, but not on trials with low cognitive load. Levels of perceived chronic stress showed a trend for a positive association with working memory maintenance, independently of cognitive load. The pattern of results remained unchanged after introduction of HRV as a mediator. Results indicate that despite young adulthood being characterized by peak cognitive performance, cardiorespiratory fitness influences working memory maintenance. The lack of mediating effects of HRV, indicates that this association cannot be explained by vagal influences on memory processing driven by the autonomic nervous system. As working memory is crucial for performance in many real-life domains, such as workplace and learning environments in general maintenance and promotion of cardiorespiratory fitness is encouraged. References Bayram, N., & Bilgel, N. (2008). The prevalence and socio-demographic correlations of depression, anxiety and stress among a group of university students. Social Psychiatry and Psychiatric Epidemiology, 43(8), 667-672. https://doi.org/10.1007/s00127-008-0345-x Forte, G., Favieri, F., & Casagrande, M. (2019). Heart rate variability and cognitive function: A systematic review [Mini Review]. Frontiers in Neuroscience, 13, Article 710. https://doi.org/10.3389/fnins.2019.00710 Loprinzi, P. D., & Frith, E. (2019). Protective and therapeutic effects of exercise on stress-induced memory impairment. Journal of Physiological Sciences, 69(1), 1-12. https://doi.org/10.1007/s12576-018-0638-0 Malter Cohen, M., Tottenham, N., & Casey, B. J. (2013). Translational developmental studies of stress on brain and behavior: Implications for adolescent mental health and illness? Neuroscience, 249, 53-62. https://doi.org/https://doi.org/10.1016/j.neuroscience.2013.01.023